Mammalian X homolog acts as sex chromosome in lacertid lizards - Rovatsos, M; Vukić, J; Kratochvíl, L (Heredity, 2016)
Among amniotes, squamate reptiles are especially variable in their mechanisms of sex determination; however, based largely on cytogenetic data, some lineages possess highly evolutionary stable sex chromosomes. The still very limited knowledge of the genetic content of squamate sex chromosomes precludes a reliable reconstruction of the evolutionary history of sex determination in this group and consequently in all amniotes. Female heterogamety with a degenerated W chromosome typifies the lizards of the family Lacertidae, the widely distributed Old World clade including several hundreds of species. From the liver transcriptome of the lacertid Takydromus sexlineatus female, we selected candidates for Z-specific genes as the loci lacking single-nucleotide polymorphisms. We validated the candidate genes through the comparison of the copy numbers in the female and male genomes of T. sexlineatus and another lacertid species, Lacerta agilis, by quantitative PCR that also proved to be a reliable technique for the molecular sexing of the studied species. We suggest that this novel approach is effective for the detection of Z-specific and X-specific genes in lineages with degenerated W, respectively Y chromosomes. The analyzed gene content of the Z chromosome revealed that lacertid sex chromosomes are not homologous with those of other reptiles including birds, but instead the genes have orthologs in the X-conserved region shared by viviparous mammals. It is possible that this part of the vertebrate genome was independently co-opted for the function of sex chromosomes in viviparous mammals and lacertids because of its content of genes involved in gonad differentiation.
Keywords: Animals; Mammals; Female; mapování chromozomů; ženské pohlaví; Gene Dosage; High-Throughput Nucleotide Sequencing; Chromosome Mapping; lidé; Evolution, Molecular; molekulární evoluce; stanovení celkové genové exprese; Computational Biology; pohlavní chromozomy; savci; Male; Sex Chromosomes; vysoce účinné nukleotidové sekvenování; Lizards; transkriptom; ještěři; zvířata; mužské pohlaví; Transcriptome; genová dávka; výpočetní biologie; Gene Expression Profiling; Humans